Frequency of Iron Deficiency Anemia in Patients of Inflammatory Bowel Disease at Pak Emirates Military Hospital, Rawalpindi - Awan, Marriam Hussain; Fazal, Imran; Lodhi, Muhammad Wajahat Alam; Azhar, Rimsha; Anwar, Ayesha; Tariq, Maria (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the presence of iron deficiency anemia and assess the relationship of various factors with the presence of anemia among the patients of inflammatory bowel disease reporting to Military Hospital, Rawalpindi.Study Design: Cross sectional study.Place and Duration of Study: Department of General Medicine, Pak Emirates Military Hospital Rawalpindi, from Jan to Dec 2018.Methodology: Two hundred cases were recruited in this study, which were diagnosed as inflammatory bowel disease in medical outpatient department (OPD) by a consultant medical specialist or gastroenterologist. Iron deficiency anemia was diagnosed on the basis of hemoglobin and ferritin levels. Relationship of age, gender, duration of inflammatory bowel disease, type of inflammatory bowel disease and poly-pharmacy was taken into account with the presence of iron deficiency anemia among the patients suffering from inflammatory bowel disease.Results: A total of 106 patients were males and 94 were females. Most common type of inflammatory bowel disease was ulcerative colitis 118 (59%). Out of 200 patients of inflammatory bowel disease, 111 (44.5%) showed the presence of iron deficiency anemia while 89 (55.5%). Long duration of illness and poly-pharmacy had a significant correlation (p-value